2012
DOI: 10.5505/tjh.2012.39205
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Genetics of von Willebrand Disease

Abstract: Quantitative and/or qualitative deficiency of von Willebrand factor (vWF) is associated with the most common inherited bleeding disease von Willebrand disease (vWD). vWD is a complex disease with clinical and genetic heterogeneity. Incomplete penetrance and variable expression due to genetic and environmental factors contribute to its complexity. vWD also has a complex molecular pathogenesis. Some vWF gene mutations are associated with the affected vWF biosynthesis and multimerization, whereas others are assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 96 publications
0
14
0
Order By: Relevance
“…Shortened survival of VWF plasma levels after desmopressin (DDAVP) is typical in these patients. 15,35 Quantitative VWF deficiency may be caused by mutations that lead to an increased clearance of VWF from the blood, where clearance mechanisms do not exhibit strong preference for large multimer VWF. The mutation p.Arg1205His causes VWD-type Vicenza, which is characterized by VWF:Ag < 15 IU/dL, and plasma multimers of VWF are sometimes even larger than those in normal plasma.…”
Section: Type 1 Von Willebrand Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Shortened survival of VWF plasma levels after desmopressin (DDAVP) is typical in these patients. 15,35 Quantitative VWF deficiency may be caused by mutations that lead to an increased clearance of VWF from the blood, where clearance mechanisms do not exhibit strong preference for large multimer VWF. The mutation p.Arg1205His causes VWD-type Vicenza, which is characterized by VWF:Ag < 15 IU/dL, and plasma multimers of VWF are sometimes even larger than those in normal plasma.…”
Section: Type 1 Von Willebrand Diseasementioning
confidence: 99%
“…The cause is the probable effect of structural changes on interactions between VWF and ADAMTS-13. 35,45,46 Group 1 mutations usually result in more severe bleeding phenotype than group 2 mutations, and patients respond better to DDAVP treatment. 35 In type 2A, four "subgroups" have been reported (IIA, IIC, IID, IIE; ►Table 1), which can be distinguished based on the multimer pattern as a result of different mutational mechanisms.…”
Section: Type 2a Von Willebrand Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Although type 1 vWD can be treated with intravenous desmopressin, in cases of type 2 and type 3, administration of intravenous vWF concentrate is likely to be necessary. Therefore, genetic confirmation is important for accurately differentiating between the subtypes of vWD and thus determining the optimal treatment approach . In this study, all of the patient's immediate family members were suspected to have vWD, and as the inheritance pattern of vWD can be unpredictable, genetic testing was performed for confirmation of the disease.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, genetic confirmation is important for accurately differentiating between the subtypes of vWD and thus determining the optimal treatment approach. 20 In this study, all of the patient's immediate family members were suspected to have vWD, and as the inheritance pattern of vWD can be unpredictable, genetic testing was performed for confirmation of the disease. Genetic analysis revealed that the patient possessed not only a previously known variant of type 1 vWD, 14,15 but also a variant known in type 2A vWD, 16 which is a highly unique pattern of vWD.…”
Section: Discussionmentioning
confidence: 99%